Exercise Training as Therapeutic Approach in Cancer Cachexia: A Review of Potential Anti-inflammatory Effect on Muscle Wasting - Leal, Luana G.; Lopes, Magno A.; Peres, Sidney B.; Batista, Miguel L. (Frontiers in Physiology, 2021)
Cancer-associated cachexia (CC) is common in the advanced stages of cancer and contributes to reducing the quality of life and expectancy of patients. CC is a significant cause of morbidity and mortality, affecting more than 80% of individuals with advanced cancer and accounting for more than 20% of deaths. It has been recognized for a long time as an adverse effect of disease and is associated with reduced physical function, tolerance to anticancer therapy, and survival Nowadays, CC has been defined as a multifactorial inflammatory syndrome with high prevalence in cancer patients, primarily characterized by metabolic chaos culminating in drastic bodyweight loss, mainly due to skeletal muscle and fat depletion. Currently, there is not a standard intervention for CC, but it is believed that a dynamic approach should be applied early in the course of the disease to maintain or slow the loss of physical function. The present review sought to explore the distinctive clinical and experimental studies of different types of exercise training and their possible contribution to a better prognosis of the syndrome. Also, the review discusses the advances in the knowledge about how exercise training may help to attenuate muscle wasting and highlight the main clinical trials that present not only the impacts of exercise in front of CC but also the challenges of its application in clinical practice.